Paraganglioma of the tongue with SDHB gene mutation in a patient with Graves' disease. Issue 4 (2nd March 2019) - Duran Alvarez, Marcela Adriana; Tavarez Rodriguez, Juan Jose; Robledo, Mercedes
Key Clinical Message: We report a case of an apparently sporadic paraganglioma of the tongue with a germ‐line mutation in a female patient with asymptomatic Graves' disease. The tongue is an unusual primary location. Genetic testing is mandatory in all cases. Thyroid gland dysfunction and autoimmune phenomena could be associated with some paragangliomas. Abstract : We report a case of an apparently sporadic paraganglioma of the tongue with a germline mutation in a female patient with asymptomatic Graves' disease. The tongue is an unusual primary location. Genetic testing is mandatory in all cases. Thyroid gland dysfunction and autoimmune phenomena could be associated with some paragangliomas.